Pulmonary Arteriovenous Malformations Incidentalloma in a 10-Years-Old Child - Daoud Ali Mohamed MhD; Amarkak Waiss MhD; Behyamet Onka MhD; Walid Mohamed MhD; Nazik Allali PhD; Latifa Chat PhD; Siham El Haddad PhD (SAGE Publishing, 2021)
Pulmonary Arteriovenous Malformations (PAVMs) are structurally abnormal vascular communications between pulmonary arteries and pulmonary veins, which bypass the normal capillary bed and cause a low resistance right-to-left shunt with refractory hypoxemia. Generally, PAVMs were congenital, most commonly associated with (Hereditary hemorrhagic teleangiectasia (HHT). The age of diagnosis is very variable, range neonatal to adulthood, mostly diagnosed in the first 3 decades of life and clinical manifestations occur later in life generally. Here, we report PAVMs discovered incidentally in a 10-years-old child without any known risk factor.